Assessing the Impact of Climate Change on Coastal Erosion and Sea-Level Rise - Rifat Khursheed (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study explores the growing concerns surrounding the effects of climate change on coastal zones, focusing specifically on coastal erosion and sea-level rise. Coastal regions, being dynamic interfaces between land and ocean, are increasingly vulnerable due to anthropogenic climate change. The research highlights the natural processes contributing to erosion, evaluates the extent of sea-level rise over recent decades, and analyzes how climatic factors intensify these phenomena. Through the use of satellite imagery, historical data, and case studies from different global coastlines, the paper assesses the socio-economic and ecological consequences of these environmental shifts. Policy recommendations are provided for sustainable coastal management and mitigation strategies.